How do Mutations of Mycobacterium Genes Cause Drug Resistance in Tuberculosis? - Hou, Kaiying; Jabeen, Riffat; Sun, Lin; Wei, Jianshe (Current Pharmaceutical Biotechnology, 2024)
A steady increase in the prevalence of drug-resistant tuberculosis (DR-TB) has already been reported in Pakistan. In addition, DR-TB is gradually changing from one-drug resistance to multi-drug resistance, which is a serious challenge for tuberculosis treatment. This review provides an overview of the anti-tuberculosis drugs and focuses on the molecular mechanisms of drug resistance in Mycobacterium tuberculosis, with the hope that it will contribute to the study of drug resistance in response to the emergence of multidrug-resistant tuberculosis.
Keywords: gene mutation